EFFECT OF DAYLIGHT EXPOSURE ON GLYCEMIC CONTROL IN ELDERLY PATIENTS WITH 2 TYPE DIABETES. LITERATURE REVIEW - Garnytska, Anna; Orlyk, Olga; Kochuieva, Maryna; Psarova, Valentyna (Eastern Ukrainian Medical Journal, 2026)
Type 2 diabetes mellitus (T2DM) is highly prevalent among older adults, and optimal glycemic control remains essential for preventing complications. Increasing evidence highlights the role of circadian rhythms and environmental factors, particularly light exposure, in glucose metabolism. Natural daylight acts as a key regulator of circadian function, whereas disruption of the light–dark cycle, especially artificial light at night, contributes to insulin resistance and impaired glycemic control. Aim of the study: to analyze current scientific evidence on the impact of natural daylight exposure on glycemic control in elderly patients with type 2 diabetes mellitus and to identify potential mechanisms underlying this effect. Object of the study: metabolic and circadian mechanisms of glycemic regulation in elderly patients with type 2 diabetes mellitus under conditions of varying exposure to natural and artificial lighting. Results: This review summarizes current clinical, experimental, and epidemiological data on the impact of light exposure on metabolic regulation in elderly patients with T2DM. Adequate daytime exposure to natural light is associated with improved glycemic control, increased time in target range, and reduced glucose variability. In contrast, nocturnal light exposure disrupts circadian regulation, suppresses melatonin, and increases the risk of metabolic disturbances. Recent studies, including randomized and large-scale epidemiological analyses, confirm that light environment significantly influences glucose homeostasis. Conclusions Circadian rhythms and light exposure are important regulators of glucose metabolism. Adequate exposure to natural daylight contributes to improved glycemic control in patients with type 2 diabetes mellitus. Excessive artificial light exposure during nighttime disrupts circadian regulation and is associated with an increased risk of insulin resistance and diabetes development. Optimization of the light–dark cycle may be considered a promising non-pharmacological component of comprehensive T2DM management in elderly patients. Further clinical studies are required to determine the optimal duration and intensity of light exposure for improving metabolic outcomes.